2022
DOI: 10.1523/eneuro.0093-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Emx1-Cre Is Expressed in Peripheral Autonomic Ganglia That Regulate Central Cardiorespiratory Functions

Abstract: The Emx1-IRES-Cre transgenic mouse is commonly used to direct genetic recombination in forebrain excitatory neurons. However, the original study reported that Emx1-Cre is also expressed embryonically in peripheral autonomic ganglia, which could potentially affect the interpretation of targeted circuitry contributing to systemic phenotypes. Here, we report that Emx1-Cre is expressed in the afferent vagus nerve system involved in autonomic cardiorespiratory regulatory pathways. Our imaging studies revealed expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that Emx1-Cre is expressed in the afferent vagus nervous system, which regulates autonomic cardiorespiratory pathways. 15 To confirm the neuronal role in mortality, ANK2 −/− :NEX-Cre mice, in which ankyrin-B was removed from excitatory neurons in the neocortex and hippocampus (but not inhibitory neurons) during embryonic development, were observed, and they also showed similar lethality ( Figure 1A ). On the contrary, seizures were not observed in ANK2 −/− :CaMKIIα-Cre mice.…”
Section: Resultsmentioning
confidence: 88%
“…Previous studies have reported that Emx1-Cre is expressed in the afferent vagus nervous system, which regulates autonomic cardiorespiratory pathways. 15 To confirm the neuronal role in mortality, ANK2 −/− :NEX-Cre mice, in which ankyrin-B was removed from excitatory neurons in the neocortex and hippocampus (but not inhibitory neurons) during embryonic development, were observed, and they also showed similar lethality ( Figure 1A ). On the contrary, seizures were not observed in ANK2 −/− :CaMKIIα-Cre mice.…”
Section: Resultsmentioning
confidence: 88%
“…Despite this, only a small subset of these animals died prematurely (Aiba and Noebels, 2021 ). However, a caveat to these experiments is that Emx1 cre/+ is not restricted to cortical excitatory neurons but rather is also expressed by peripheral autonomic ganglia that provide modulatory feedback to cardiorespiratory centers (Ning et al, 2022 ). Excluding potential confounding effects of peripheral nerves, these results suggest compromised brainstem function is required for cortical seizure- or SD-induced respiratory arrest and premature death (see Section “III.…”
Section: Spreading Depolarizationmentioning
confidence: 99%